UNDERSTANDING THE BOND BETWEEN NURSING PROFESSIONALS AND PATIENTS - Ferreira Costa Roseo, Fabianne; Ferreira Neta, Rosa; Gonçalves Arruda, Amália; Fabrício de Souza, Joice (Cadernos ESP, 2025)
Objective: To investigate the factors that strengthen attachment between nursing professionals and patients in Primary Health Care. Methodology: Descriptive and qualitative research conducted among eight nursing professionals from Arneiroz, in the state of Ceará. Data were collected through semi-structured interviews and analyzed using the technique of content analysis from Minayo. Results: The results reveled that staff turnover, work overload, and Community Health Agents’ undervalue obstruct the strengthening of bonds, while qualified listening, empathy, and continuity of healthcare stand out as facilitators. Final Considerations: We conclude that a humanized patient welcoming is essential for the Family Health Strategy consolidation, although the findings can also support the improvement of Primary Health Care in different contexts across the country.
Keywords: Welcoming; Continuity of Patient Care; Nursing